(untitled) (Indonesian Tourism Justice Review, 2024)
Indonesia’s eco-tourism sector has rapidly expanded, reflecting the country’s dual commitment to conservation and sustainable development. Despite its potential for environmental and socio-economic benefits, eco-tourism raises significant ethical questions regarding the balance between tourism promotion and the protection of Indonesia’s fragile ecosystems. This paper critically examines the ethical implications of eco-tourism in Indonesia, focusing on key regions such as Raja Ampat, Bali, and Sumatra. It highlights how eco-tourism, while generating economic benefits, often exacerbates environmental degradation and disrupts local communities. Drawing on both qualitative case studies and policy analysis, this study argues that the commercialization of natural resources, while purportedly promoting sustainability, may lead to the commodification of nature and marginalize indigenous voices. Furthermore, the research explores the role of government policies, industry certifications, and local stakeholders in ensuring the ethical management of eco-tourism. The findings suggest that eco-tourism in Indonesia must evolve into a more inclusive model, where environmental conservation and local empowerment are paramount. The paper concludes by recommending policy reforms that integrate ecological preservation with the equitable distribution of tourism profits, thereby safeguarding Indonesia’s natural heritage and ensuring long-term sustainability for local communities.